Pengaruh Gaya Kepemimpinan Kepala Desa Terhadap Disiplin Kerja Perangkat Desa : The Influence Of The Village Head’s LeadeHrship Style On The Work Discpline Of Village Officials - Ariwijaya, Heny; Rusman, Liswan; Intan, Nur; Kasiang, Siti Fadila (Jurnal Ilmiah Produktif, 2024)
The purpose of this study was to determine the effect of the village head's leadership style on the work discipline of village officials in Tou Village, Moilong District. This study is a type of quantitative research using a simple linear regression analysis method and using 11 samples based on data processing with the help of the SPSS program, a simple linear regression equation Y = 6.304 + 0.457X was obtained. The constant value of 6.304 means that if it is not influenced by the leadership style variable, work discipline is 6.304. The leadership style variable (X) has a significant effect on work discipline (Y). This is indicated by the correlation coefficient value (r) of 0.788 or is in the interval of 0.60 - 0.799, meaning that the relationship between the independent variable of leadership style and the dependent variable of work discipline has a strong relationship. The coefficient of determination (r²) of 0.621 indicates the percentage of influence or contribution of the independent variable in explaining the dependent variable, which is 62.1% and the rest is explained by variables other than the variables being tested. Through the t-test of variable X, Tcount > Ttable = 3.845 > 2.306 was obtained, which means that there is a significant influence of the leadership style variable (X) on the work discipline variable (Y).